Blockchain as a service : understanding the landscape and potential benefits - Kilroy, Karen (O'Reilly Media, 2019)
While the merits of cryptocurrency continue to be debated, the underlying technology--the blockchain--can be applied in many other ways to solve problems that have plagued organizations for years. To spur adoption of blockchain for these newer use cases, many technology providers and leading businesses have begun offering cloud-based blockchain-as-a-service (BaaS) options. This report brings you up to speed on these emerging opportunities. Author Karen Kilroy helps technical business leaders, solutions architects, and innovation officers understand blockchain and evaluate options for BaaS. Through interviews with enterprise blockchain experts and practitioners, you'll learn how this service model has evolved and what it offers. You'll also examine the landscape of BaaS offerings, get a project started, and learn where the technology is going. You'll learn: Why blockchain is different from a relational database or other distributed ledger technologies How blockchain is used in business applications The nuts and bolts of a blockchain network, including participants, assets, transactions, and smart contracts How to architect a typical BaaS application as a standalone multiuser application Current BaaS offerings and how to choose the one that's right for you Five industry-changing use cases for BaaS, including international trade, identity verification, and royalties tracking Examples of how BaaS may be used in the future.